TRAF2 Controls Death Receptor-Induced Caspase-8 Processing and Facilitates Proinflammatory Signaling - Kreckel, Jennifer; Anany, Mohammed A.; Siegmund, Daniela; Wajant, Harald (Frontiers in Immunology, 2019)
Tumor necrosis factor (TNF) receptor associated factor-2 (TRAF2) knockout cells were generated to investigate the role of TRAF2 in signaling by TNFR1 and the CD95-type death receptors (DR) TRAILR1/2 and CD95. To prevent negative selection effects arising from the increased cell death sensitivity of TRAF2-deficient cells, cell lines were used for the generation of the TRAF2 knockout (KO) variants that were protected from DR-induced apoptosis downstream of caspase-8 activation. As already described in the literature, TRAF2 KO cells displayed enhanced constitutive alternative NFκB signaling and reduced TNFR1-induced activation of the classical NFκB pathway. There was furthermore a significant but only partial reduction in CD95-type DR-induced upregulation of the proinflammatory NFκB-regulated cytokine interleukin-8 (IL8), which could be reversed by reexpression of TRAF2. In contrast, expression of the TRAF2-related TRAF1 protein failed to functionally restore TRAF2 deficiency. TRAF2-deficiency resulted furthermore in enhanced procaspase-8 processing by DRs but this surprisingly came along with a reduction in net caspase-8 activity. In sum our data argues i) for a non-obligate promoting function of TRAF2 in proinflammatory DR signaling and ii) a yet not recognized stabilizing effect of TRAF2 on caspase-8 activity.